Separation leaching of an arsenical copper concentrate - Ducusin, Ruben M.
By their nature, arsenic-bearing minerals are difficultly soluble, requiring elevated temperatures and pressures, along with corrosive environments to effect dissolution. Furthermore, the production of arsenic compounds generally interferes with subsequent methods of treatment to separate other metals from it. This study evaluates the rate of dissolution of Lepanto arsenical copper concentrate in acid oxidative pressure leaching conditions. It is known that arsenic forms compounds with iron which are insoluble even in highly acid conditions. This aspect was considered with respect to the production of a pregnant liquor sufficiently low in arsenic. A further aspect of this work relates to the use of pyrite, not only to supply iron for arsenic precipitation, but to generate sulfuric acid for dissolution as well, through oxidation mechanisms. Effects of temperature, oxygen overpressure, stirring, and pyrite additions were evaluated. Studies were made in the temperature range 125° to 225°C, and pressures of 25 to 970 p.s.i.a. of oxygen. The dependency of the rate of leaching on oxygen overpressure was explained in terms of adsorption of oxygen on the surface of enargite, followed by changes in the adsorbed state, thereby making it prone to the action of acid. These studies have shown that enargite can be dissolved readily to high values of copper extraction, with minimal amounts of arsenic in solution, with only copper concentrate, pyrite, and oxygen involved